تقييم نتائج تفتيت الحصيات الكلوية بالأمواج الصادمة من خارج الجسم - حرفوش أيمن; ناصر حسان; سفر مهند (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 152 مريضاً حصلنا على نتائج إيجابيةٍ عند 93 مريضاً أي 61,2% والنتيجة الإيجابية هي التخلص نهائيا" من الحصيات أو بقاء قطعٍ صغيرة لايتجاوز أكبرها 4 ملم تناولنا أيضا" في دراستنا تأثير بعض العوامل في نتائج التفتيت كالعمر, الجنس, التواتر, عدد الجلسات, عدد الحصيات وحجمها وتوضعها, الأدوية المتناولة, طريقة التسكين وغيرها من حيث المضاعفات فقد ناقشنا جميع المضاعفات الحاصلة في المركز مع نسبها ورأينا أن أكثر المضاعفات تواتراً كان الشارع الحصوي 8% كما قمنا بمقارنة نتائجنا مع أربع دراساتٍ عالمية و أشرنا إلى مواقع التوافق ومواقع الاختلاف Our study involved 152 patients; we got positive results in 93 patients (61.2%). The positive results meant that the kidney was free of stones or had small pieces of <4mm remaining. Also, we dealt with the effect of many factors on the results, such as age, sex, frequency, number of sessions, number, size, and place of stones, medicine taken, and method of anesthesia, etc. As for complications, we discussed all the complications and their rate that occurred at the center; we found that the most frequent complication was the steine strasse (8%). We also compared our results with four international studies and mentioned those points of similarity and difference.